2009
DOI: 10.4314/eajph.v5i3.39001
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Of Hiv, Sexua Behagior And Correlates Of Risky Sex Among Street Children In Kinshasa, Democratic Republic Of Congo

Abstract: Context: Homeless children are at risk of getting many diseases, including sexually transmitted infections (STI). The number of street children is on the rise in the Democratic Republic of Congo (DRC), while very little is known about their health problems. Objectives: To determine knowledge of HIV (transmission and prevention means), sexual activity, exposure to HIV-prevention services, and to identify correlates of risky sexual behaviour (not having used a condom at first or last sexual encounter and/or havi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
45
1
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(58 citation statements)
references
References 34 publications
(33 reference statements)
7
45
1
5
Order By: Relevance
“…Concurrently, different studies showed that there are rampant sexual activities among street children and with others in the community [3] [5]. In this study, (46.4%) of street children were proven be involved in sexual intercourse which is lower than the previous study conducted among street children in Democratic Republic of Congo (85.5%) and Egypt (67%) [12] [13]. This variation could be due to the difference in the age group of the study subjects, as this study included younger (10 -18 years old).…”
Section: Discussionmentioning
confidence: 53%
“…Concurrently, different studies showed that there are rampant sexual activities among street children and with others in the community [3] [5]. In this study, (46.4%) of street children were proven be involved in sexual intercourse which is lower than the previous study conducted among street children in Democratic Republic of Congo (85.5%) and Egypt (67%) [12] [13]. This variation could be due to the difference in the age group of the study subjects, as this study included younger (10 -18 years old).…”
Section: Discussionmentioning
confidence: 53%
“…In the present study, the mean age at the first sexual intercourse was 20.85 years compared to 17.6-18.0 years in Northern Thailand (Allen et al, 2003;Liu et al, 2006), 13.0-16.2 in America (Zelnik et al, 1983;Coker et al, 1994;De Genna et al, 2011), 14.0-16.8 in Europe (Andersson-Ellstrom et al, 1996Wellings et al, 1996;Edgardh, 2000;Woynarowska et al, 2006;Panatto et al, 2012) and 13.5-17.8 in Africa (Kayembe et al, 2008 ;Dingeta et al, 2012;Doku, 2012;Remes et al, 2012). The delay of first sexual intercourse in the current study may have been influenced by Thai traditional culture, in which early experience with sexual intercourse is considered socially unacceptable (Sridawruang et al, 2010;Supametaporn et al, 2010).…”
Section: Discussionmentioning
confidence: 95%
“…5 Studies have also acknowledged the high HIV risk in this population. 11,12 Due to the relative paucity of evidence available, little is known about the epidemiology or public health impact of disease amongst this population.…”
Section: Introductionmentioning
confidence: 99%